Thermal characteristics analysis of an IGBT using a fiber Bragg grating - Bazzo, João Paulo (2012)
This paper proposes a new method to develop a thermal model of an insulated gate bipolar transistor (IGBT) employing an optical fiber sensor mounted on the chip structure. Some features of the sensor such as electromagnetic immunity, small size and fast response time, allow the identification of temperature changes generated by the energy loss during device operation through direct measurement. In fact, this measurement method is considered impossible with conventional sensors. The online monitoring of the junction temperature enables identify the thermal characteristics of the IGBT. The results are used to develop an accurate model to simulate the heat generated during the device conduction and switching processes. The model showed a difference of only 0.3% between the measured and simulated results, besides allowing evaluate separately the heat generated by each turn-ON/OFF process.